Retrospective analysis of treatment-naive Slovenian patients with metastatic melanoma treated with pembrolizumab - Hribernik, Nežka (Radiology and oncology (Ljubljana), 2020)
Based on recent data from clinical trials, the immune checkpoint inhibitor pembrolizumab prolongs survival and has a good toxicity profile in patients with advanced or metastatic melanoma. However, the question remains whether these results are transmitted into daily clinical practice. The aim of this study was to assess the efficacy and toxicity of pembrolizumab in treatment-naive patients with metastatic melanoma in everyday clinical practice in Slovenia and compare it to the results from clinical trials. Patients and methods. This observational retrospective cohort study included 138 consecutive metastatic treatment-naive melanoma patients treated with pembrolizumab at the Institute of Oncology Ljubljana in Slovenia, from January 2016 to December 2018. Patient and treatment characteristics were retrospectively collected from hospital data base. Statistical data was obtained using the SPSS software version 22. Survival rate was calculated with the Kaplan-Meier method. Observation period took place between January 2016 and the end of June 2019. Results. The estimated median overall survival (OS) was 25.1 months (95% CI, 14.6%35.6) and the median progressionfree survival (PFS) was 10.7 months (95% CI, 5.9%15.4). Among all patients, 29 (21.0%) achieved complete response, 31 (22.5%) partial response and 23 (16.7%) reached stable disease. The number of organs with metastatic involvement and the level of baseline lactate dehydrogenase (LDH) concentration had significant influence on survival rates. Immune-related adverse events (irAE) were reported in 88 (63%) patients, while grade 3%4 irAE occurred in 12 (8.7%). Due to toxicity, 16 (11.6%) patients discontinued the treatment. Conclusions. Our real-world data from single centre retrospective analysis of treatment-naive metastatic melanoma patients treated with pembrolizumab showed inferior median OS and similar median PFS, compared to the results from clinical trials. However, patients with normal serum levels of LDH and a small number of organs with metastatic involvement had comparable survival outcomes. Toxicity rates of pembrolizumab were quite similar. These results further support the use of pembrolizumab for metastatic treatment-naive melanoma patients.
Keywords: imunoterapija; metastaski melanom; pembrolizumab; zdravljenje